2022
DOI: 10.3390/plants11030401
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Changes in Macrophyte Distribution and Abundance in a Lowland River

Abstract: The aim of this study was to reveal the changes of macrophyte community over time and along the course of the Ižica River. In 1996, 2000, and 2016, we surveyed the distribution and abundance of macrophyte species in the lowland Ižica River, which originates in the town of Ig and then flows through an agricultural landscape. We calculated the River Macrophyte Index (RMI), which reflects the ecological status of the river. In 2016, ecomorphological conditions of the river, using the Riparian, Channel and Environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Similarly, functional evenness was higher at fine substrates (p=0.002) which confirms a possible association of increased functional diversity with soft and fine river substrates. Previous studies have shown that geomorphological features such as river bottom type, substrate structure and riverbank stability are important factors for explaining macrophyte composition in lotic ecosystems (Peternel et al, 2022). Rooted aquatic plants in particular, prefer fine sediments (Willby et al, 2000;Hrivnaḱ et al, 2010) while bryophytes usually occur at coarser substrates, such as boulders and cobbles.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, functional evenness was higher at fine substrates (p=0.002) which confirms a possible association of increased functional diversity with soft and fine river substrates. Previous studies have shown that geomorphological features such as river bottom type, substrate structure and riverbank stability are important factors for explaining macrophyte composition in lotic ecosystems (Peternel et al, 2022). Rooted aquatic plants in particular, prefer fine sediments (Willby et al, 2000;Hrivnaḱ et al, 2010) while bryophytes usually occur at coarser substrates, such as boulders and cobbles.…”
Section: Discussionmentioning
confidence: 99%
“…The articles of Peternel et al [ 11 ] and Panzeca et al [ 12 ] present two different examples in which macrophytes are used to characterize aquatic environments, in a river in Slovenia and in farm ponds of a district of Sicily, respectively. The species composition of the macrophyte community revealed significant changes over the years in a riverine ecosystem in the first case, whereas in the second one it was shown that, although farm ponds are artificial and relatively poor habitats, they seem to be important for aquatic flora and the conservation of local biodiversity.…”
Section: Special Issue Contentsmentioning
confidence: 99%